Biochemical Composition of Some Turkish Fungi - COLAK, AHMET; KOLCUOGLU, YAKUP; SESLI, ERTUGRUL; DALMAN, OMER (Asian Journal of Chemistry, 2010)
The fructification organs of Macrolepiota mastoidea, Lepista nuda, Handkea excipuliformis, Amanita rubescens and Boletus queletii were analyzed in terms of moisture, nitrogen, protein, crude fat, carbohydrate, vitamin C, ash, energy values and trace element contents (Zn, Mn, Fe, Cu, Cd, Pb, Co and Ni). The chemical composition of the specimens in dried matter g/100 g, moisture 74.03-92.5 %, nitrogen 4.36-7.08 %, protein 27.30-44.20 %, crude fat 2.70-27.50 %, total carbohydrate 29.70-65.30 %, vitamin C 0.01-0.05 %, ash 2.00-10.00 % and energy 397.66-493.90 kcal/100 g. The trace element contents of specimens were determined by atomic absorption spectrometry after microwave digestion. The results were (as mg/kg) 34.4-47.0 zinc, 22.8-100.0 manganese, 13.7-44.9 iron, 3.9-19.3 copper, 0.2-0.7 lead, 0.4-0.5 cobalt and 1.2-2.2 cadmium. These results make these edible wild mushrooms popular as a food source and it can be thought that these mushrooms may be cultivated.